Biohydrogen Production During Growth of an Indigenous Bacterium, Ochrobactrum Putranensis Eb2,in Palm Oil Mill Effluent - Cheong, Weng Chung (2006)
The study was on the production of hydrogen from palm oil mill effluent using indigenous bacteria. Three potential bacteria (WL1, EB2, and DT1) were isolated from wetland soil, termite’s gut and anaerobic digester tank, respectively. All three isolates were Gram-positive, spore-forming, facultative anaerobe rods and exhibited motility by means of peritrichous flagella. All of the isolates were short straight rods, appeared in-pairs, clumped-together and formed biofilm on the agar surface. Using the 16s rRNA identification method, EB2 belonged to the Brucellaceae family and is closely related to Ochrobactrum sp., thus, designated as Ochrobactrum putranensis EB2; while WL1 and DT1 isolates were taxonomically positioned as Bacillus cereus. These bacteria differed by 30-35% in the 16s rRNA identification method from the existing bacteria recorded in the gene library. Since EB2 is different from other bacteria in the database, it is regarded as a new bacteria. In this study, the EB2 bacteria was used throughout the study to enhance the production of hydrogen. The study on the optimization of hydrogen production was done on the Ochrobactrum putranensis EB2 and the parameters chosen were pH 4, 5 and 6; at temperatures 30°C, 37°C and 45°C. Comparisons were done with VFA and hydrogen production as well as COD reduction. The Ochrobactrum putranensis EB2 was able to grow steadily in POME and produced hydrogen at the pH of 5.5 and temperature 37°C. The highest μmax obtained was 0.384 h-1. An average of 1300 mL of accumulated hydrogen volume was obtained within 72 hours of batch fermentation from 1 L of POME in the optimization study. Production of hydrogen from palm oil mill effluent (POME) by Ochrobactrum putranensis EB2 was investigated in 2.0 L bioreactor with working volume of 1.0 L at 37°C and pH of 5.5 ± 0.3. The optimized conditions were applied in the hydrogen production study. The average hydrogen volume accumulated in the system was 1100 mL with 58.0% COD removal. Repeated experiments done on the batch fermentation confirmed the reproducibility of the results. Continuous fermentation were started after 72 hours of batch fermentation when there was no hydrogen production. During continuous fermentation, hydrogen gas production was at 34.2 mL H2/L per day for HRT 0.5 day, 13.0 mL H2/L per day for HRT 1.0 day and 12.6 mL H2/L per day for HRT 1.5 days and these show the HRT-dependent characteristics of hydrogen production. The efficiency of Ochrobactrum putranensis EB2 to convert the POME into hydrogen gas was about 31.67 mL H2/g COD and was the highest recorded in batch fermentation reducing to 8 mL H2/g COD at the end of the batch fermentation. The highest productivity obtained in the continuous fermentation was 1.07 mol H2/mol glucose, was good in comparison with those reported earlier, 1.00-2.36 mol H2/mol glucose. The high productivity was excellent as most of the COD was converted to gas, based on the theoretical yield of 4 mol-H2/mol-glucose. As such, HRT 0.5 day gave the best result compared to other HRT done in the study.